Strategic Management in Islamic Banking: The Role of Religiosity and Service Satisfaction in Shaping Customer Decisions - Ahyar Junaedi; Mohamad Rafii; Bayu Suratmoko (Journal of Enterprise and Development (JED), 2024)
Purpose: This study explores the influence of religiosity and service satisfaction on customer decisions, focusing on the dynamics of these variables within the Islamic banking sector in Indonesia, one of the largest markets for Sharia-compliant financial services globally.Method: A quantitative research approach was used to collect data from 100 respondents via structured questionnaires. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to rigorously test the hypothesized relationships and evaluate the strength and direction of the proposed variables.Result: The findings indicate that religiosity has a statistically insignificant effect on customer decisions. While religious alignment may influence preferences, it does not substantially drive decision-making. In contrast, service satisfaction is a significant and dominant factor influencing customer decisions. Together, these variables account for 50.7% of the variance in customer decisions, highlighting the critical role of service quality in shaping customer behavior within the Islamic banking sector.Practical Implications for Economic Growth and Development: The study suggests that enhancing service satisfaction in the Islamic banking sector can significantly drive customer decisions, thereby contributing to economic growth and development by strengthening consumer trust and increasing market participation.